Variation of carrying angle with age, sex, and special reference to side - Yilmaz, E; Karakurt, L; Belhan, O; Bulut, M; Serin, E; Avci, M (Slack Inc, 2005)
We measured the carrying angle using a universal full-circle manual goniometer on the dominant and non-dominant extremity of the elbow in 1275 healthy volunteers (631 males, 644 females) with a mean age of 22.87 +/- 15.99 years (range: 2-91 years). In the right arm dominant group, right carrying angle was 11.25 degrees +/- 3.73 degrees and left carrying angle was 10.57 degrees +/- 3.63 degrees (P <.001). In left arm dominant group, right carrying angle was 10.65 degrees +/- 3.99 degrees and left carrying angle was 12.93 degrees +/- 4.22 degrees (P <.001). The carrying angle of dominant arm was found to be significantly higher than the non-dominant arm in both sexes. The carrying angle of dominant and non-dominant arms were found to be significantly higher in patients aged > 14 years than that of patients aged <= 14 years; females ranked higher than males.
Keywords: Elbow; Forearm; Motion; Range